2021
DOI: 10.1016/j.chest.2020.10.067
|View full text |Cite
|
Sign up to set email alerts
|

A Clinic Blueprint for Post-Coronavirus Disease 2019 RECOVERY

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic poses extraordinary challenges. The tremendous number of coronavirus disease 2019 (COVID-19) cases in the United States has resulted in a large population of survivors with prolonged post-infectious symptoms. The creation of multidisciplinary post-COVID-19 clinics to address both persistent symptoms and potential long-term complications requires an understanding of the acute disease and the emerging data regarding COVID-19 outcomes. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 73 publications
2
67
0
7
Order By: Relevance
“…In early studies, COVID-19 survivors have presented a spectrum of persistent pulmonary dysfunction, and they are expected to have a high prevalence of post-intensive care syndrome, which encompasses reduced physical, cognitive, and mental health after critical illness. 27 Therefore maintenance dialysis patients who survive COVID-19 may benefit from interdisciplinary post-hospitalization care. Lastly, this study and others demonstrate that mortality exceeds 20% among maintenance dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, COVID-19 survivors have presented a spectrum of persistent pulmonary dysfunction, and they are expected to have a high prevalence of post-intensive care syndrome, which encompasses reduced physical, cognitive, and mental health after critical illness. 27 Therefore maintenance dialysis patients who survive COVID-19 may benefit from interdisciplinary post-hospitalization care. Lastly, this study and others demonstrate that mortality exceeds 20% among maintenance dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many unknowns remain on what proportion of COVID-19 survivors will require multidisciplinary post-COVID-19 clinics to address both persistent symptoms and potential long-term respiratory and other complications ( i.e. : acute kidney injury, myocarditis, psychiatric outcomes, …) [ 21 ]. And on what standard treatments and management strategies should be applied [ 22 ], most likely to be periodically revisited whenever new, significant evidence be available.…”
Section: Textmentioning
confidence: 99%
“…: acute kidney injury, myocarditis, psychiatric outcomes, …). 21 And on what standard treatments and management strategies should be applied, 22 most likely to be periodically revisited whenever new, significant evidence be available. It will be another toll of this pandemic, to add up to the global risks we face in these most uncertain times.…”
Section: Textmentioning
confidence: 99%
“…Remdesivir and dexamethasone has been proved effective in hospitalized patients with COVID-19 in recent clinical trials [7,8]. As the number of recovered patients accumulate, there is a growing need to understand evolving aspects of clinical, radiological, and functional outcomes [10][11][12] Post-illness outcome studies pertaining to other Coronavirus infections, Severe Acute Respiratory Syndrome (SARS) and Middle East respiratory syndrome (MERS), have demonstrated some patients to experience long-term respiratory impairment in the recovery phase [13][14][15]. Recent studies showed some patients with COVID-19 pneumonia to manifest persistent symptoms and residual abnormalities on chest CT scans at 3-4 months after discharge [16][17][18].…”
Section: Introductionmentioning
confidence: 99%